2010
DOI: 10.1002/iub.405
|View full text |Cite
|
Sign up to set email alerts
|

A role for human neuroglobin in apoptosis

Abstract: SummaryOver the past decade, following the discovery of the human heme protein neuroglobin, many studies have searched for evidence for this protein's mechanism of action. Much data has accrued showing that high levels of neuroglobin will protect cells from apoptotic cell death, following a wide range of challenges. Various explanations of its actions, based on measured reactivity with oxygen, nitric oxide, or free radicals, have been proposed, but none have, as yet, been substantiated in vivo. Following preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 63 publications
0
64
0
Order By: Relevance
“…The globin fold also enables the tissue hemoglobin to serve as either a facilitator of oxygen transport within a cell, a scavenger of nitric oxide, and/or an enzyme with peroxidase activity. Hemoproteins such as cytoglobin (CYGB) neuroglobin (Ngb) have been implicated in mediating neurorestorative responses in models of hypoxia-ischemia and spinal cord trauma [5860]. Although LC-O3PUFAs may also prevent the degradation of these key proteins, the effects of dietary LC-O3PUFAs on this important family needs to be clarified and further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…The globin fold also enables the tissue hemoglobin to serve as either a facilitator of oxygen transport within a cell, a scavenger of nitric oxide, and/or an enzyme with peroxidase activity. Hemoproteins such as cytoglobin (CYGB) neuroglobin (Ngb) have been implicated in mediating neurorestorative responses in models of hypoxia-ischemia and spinal cord trauma [5860]. Although LC-O3PUFAs may also prevent the degradation of these key proteins, the effects of dietary LC-O3PUFAs on this important family needs to be clarified and further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Brittain et al and Yu et al [12,58], in many of the above mentioned studies, where NGB exhibited a significant effect on nerve cell survival, parameters linked to mitochondrial functions were significantly affected by NGB expression. They include ATP production [45] and reactive oxygen species (ROS) generation [34,39,48].…”
Section: Possible Mechanisms Of Ngb Neuroprotectionmentioning
confidence: 89%
“…These findings, together with evidence showing that NGB expression is basically confined to metabolically active, oxygen-consuming cell types (see Section 2.1), led to the hypothesis that mechanisms triggered by NGB could induce neuroprotection by modulating mitochondria function and regulation (see [12,58] for reviews). The exact processes, however, are still under careful investigation.…”
Section: Possible Mechanisms Of Ngb Neuroprotectionmentioning
confidence: 99%
“…An increased level of Ngb expression also promotes neuron survival after ischemic insults (Sun et al, 2001;Sun et al, 2003). The molecular basis of the neuroprotective function of Ngb remains unclear, but several plausible mechanisms have been proposed, including oxygen storage (Dewilde et al, 2001;Sun et al, 2001), oxygen/redox sensing (Wakasugi et al, 2003), decomposition of reactive oxygen species (Herold et al, 2004;Van Doorslaer et al, 2003), and inhibition of apoptosis (Brittain et al, 2010a;Fago et al, 2006). In addition, Wakasugi et al (2003) reported that ferric Ngb binds to the GDP-bound form of the α-subunit of the heterotrimeric G protein acting as a guanine nucleotide dissociation inhibitor and the interactions between hNgb and the G protein may promote cell survival (Wakasugi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wakasugi et al (2003) reported that ferric Ngb binds to the GDP-bound form of the α-subunit of the heterotrimeric G protein acting as a guanine nucleotide dissociation inhibitor and the interactions between hNgb and the G protein may promote cell survival (Wakasugi et al, 2011). Alternatively, Brittain et al (2010a;2010b) showed that in vivo Ngb inhibits apoptosis through the binding to cytochrome c and preventing pro-caspase 9 activation.…”
Section: Introductionmentioning
confidence: 99%